The Influence of Price, Quality of Service and Promotions on Customer Satisfaction at Bu Rajab Resto Pancing and Cottage - Muhammad, Rabhi Fathan; Melinda, Tina (KnE Social Sciences, 2021)
This study was conducted to analyze the influence of price (X1), service quality (X2) and promotions (X3) on customer satisfaction at Bu Rajab Resto Pancing and Cottage. The study used a quantitative approach and was conducted from March to June 2020. Purposive sampling was used. 120 people were included in the research and 97 people were selected as samples. Participants were customers of Bu Rajab Resto Pancing and Cottage who had visited at least 2 times. A questionnaire was used for data collection. Data analysis involved linear regression, hypothesis testing and classical assumption tests, using the SPSS program. Price and service quality had a significantly positive impact on customer satisfaction, but promotions did not. Keywords: price, service quality, promotion, customer satisfaction